Surgimento e trajetória do Estado Islâmico - Júnior Damin, Cláudio (2017)
The article describes the emergence and trajectory of the insurgent group called the Islamic State, analyzing its transformations over time. Former affiliate of al-Qaeda in Iraq, this terrorist organization claims to be a state, governs territories, keeps an irregular army and is considered an existential threat to Middle East countries.